Power Allocation for Cognitive Relay System over Rayleigh Fading Channels - Rouhollah Aghajani; Reza Saadat; Mohammad Reza Aref (Journal of Intelligent Procedures in Electrical Technology, 2013)
In this paper we consider two networks, a primary network and a secondary cooperative communication network. In the secondary network, a source is assisted by cognitive relay nodes which allow it to coexist with the primary network. The secondary users must work under the noise floor of the primary network to achieve low interference for the primary network. Simultaneously, the secondary users should be able to complete their duty. Therefore, the cooperative system utilizes the incremental and selective decode-and-forward (ISDF) relaying protocols. In ISDF protocol, the relay sends signal in necessary situations. Thus, the ISDF cooperative scheme is considered for the secondary network in order to reduce the interference to the primary users. Under some constraints on the transmitting power from the source and relay nodes in the secondary network, they can operate below the noise level of the primary network. Under these constraints, we minimize the symbol error rate of the secondary network. It is seen that in the ISDF protocol the interference produced with the relay to the primary users is very low.